The Determinants of Enterprise Risk Management (ERM) Practices in Malaysian Public Listed Companies - Razali, Ahmad Rizal; ., Izah Mohd Tahir (Journal of Social and Development Sciences, 2011)
The objective of this study is to examine the determinants of Enterprise Risk Management (ERM) adoption in Malaysian Public Listed Companies (PLCs). The study focuses on ten industries from five hundred and seventy four Public Listed Companies in Malaysia for the period 2007. These ten industries include industrial products, trading/services, consumer products, properties, constructions, plantations, infrastructure projects, technology, hotels and mining. Logit regression approach will be employed, and a dummy variable equals one if companies adopt ERM and zero otherwise, is used as the dependent variable. Seven independent variables used are Size, Leverage, Profitability, International Diversification, Ownership, Chief Risk Officer and Turnover. The main results of this research is that companies with high turnover, hiring Chief Risk Officer and companies that are not diversified internationally are more likely to adopt ERM. Interestingly, Size, Leverage, Profitability, and Ownership are not significant determinants of ERM practices.